2022
DOI: 10.3389/fimmu.2022.883375
|View full text |Cite
|
Sign up to set email alerts
|

Th2 to Th1 Transition Is Required for Induction of Skin Lesions in an Inducible and Recurrent Murine Model of Cutaneous Lupus–Like Inflammation

Abstract: Cutaneous lupus erythematosus (CLE) is an autoimmune skin disease characterized by a strong IFN signature, normally associated with type I IFNs. However, increasing evidence points to an additional role for IFNγ, or at least a pathogenic T effector subset dependent on IFNγ, for disease progression. Nevertheless, Th2 effector subsets have also been implicated in CLE. We have now assessed the role of specific T cell subsets in the initiation and persistence of skin disease using a T cell-inducible murine model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Vitiligo and lichen planus were prevalent in two cases, while cutaneous lupus erythematosus and pemphigus foliaceus occurred in one instance. These autoimmune diseases correspond to the pathogenesis of alopecia areata because vitiligo, lichen planus, and lupus erythematosus, excluding pemphigus foliaceus, are Th1‐significant immunological states 22–24 . Interestingly, vitiligo and lichen planus were observed in the same individuals, suggesting a possible Th1‐dominant state in these patients.…”
Section: Discussionmentioning
confidence: 82%
“…Vitiligo and lichen planus were prevalent in two cases, while cutaneous lupus erythematosus and pemphigus foliaceus occurred in one instance. These autoimmune diseases correspond to the pathogenesis of alopecia areata because vitiligo, lichen planus, and lupus erythematosus, excluding pemphigus foliaceus, are Th1‐significant immunological states 22–24 . Interestingly, vitiligo and lichen planus were observed in the same individuals, suggesting a possible Th1‐dominant state in these patients.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, the study of vaccination (BNT162b2) in current use revealed some Th2-skewed immune response as well as well-known Th1-skewed immune response ( 14 ); therefore, vaccine-induced atypical deleterious Th2 immunity overlapping with normal Th1 immunity may contribute to the pathogenesis of prodromal erythema. Also, Th2 to Th1 transition was reported to be required for the maintenance and potentiating of skin inflammation by the in vivo analysis of cutaneous lupus erythematosus model mice ( 15 ); therefore, Th2 to Th1 transition may contribute to refractory vitiligo in the current case. Considering the consistent Th1-skewed response in idiopathic VKH syndrome, the fundamentals of aetiological and clinical features in the current case could be considered to be due to Th2-modified idiopathic VKH syndrome.…”
Section: Discussionmentioning
confidence: 91%
“…Recent work in a murine CLE model suggests that initial skin infiltration with Th2 cells and re‐polarization to Th1 T RM is required for persistence of CLE skin eruptions. Th1‐polarized T RM produce IFN‐γ and maintain their phenotype in disease recurrence 204,209 . As in addition IL‐15‐induced circulating CD4 + T cells with cytotoxic properties were recently found in systemic lupus erythematosus, 210 future studies of skin T cells in CLE may offer interesting insights into epigenetic potential of CD4 + T RM .…”
Section: Trm In Disease Pathogenesismentioning
confidence: 99%